2021
DOI: 10.1038/s41598-021-98462-2
|View full text |Cite
|
Sign up to set email alerts
|

PaCO2-management in the neuro-critical care of patients with subarachnoid hemorrhage

Abstract: The partial pressure of carbon dioxide (PaCO2) in the arterial blood is a strong vasomodulator affecting cerebral blood flow and the risk of cerebral edema and ischemia after acute brain injury. In turn, both complications are related to poor outcome in patients with aneurysmal subarachnoid hemorrhage (aSAH). We aimed to analyze the effect of PaCO2 levels on the course and outcome of aSAH. All patients of a single institution treated for aSAH over 13.5 years were included (n = 633). Daily PaCO2 values from art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Our study revealed that the elevated PaCO 2 levels in COPD patients are an independent risk factor for developing delirium or cognitive impairment. Arterial blood PaCO 2 levels can impact cerebral blood ow and intracranial pressure, with higher levels of PaCO 2 resulting in increased intracranial pressure [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that the elevated PaCO 2 levels in COPD patients are an independent risk factor for developing delirium or cognitive impairment. Arterial blood PaCO 2 levels can impact cerebral blood ow and intracranial pressure, with higher levels of PaCO 2 resulting in increased intracranial pressure [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in CBF, which happens secondary to a change in PaCO 2 , is termed as cerebrovascular reactivity to carbon dioxide (CVR-CO 2 ). [ 9 ] Studies have shown that both TIVA and INHA have variable effects on CVR-CO 2 , and the effect of these agents on CVR also differs with many physiological and pathologic conditions. [ 10 11 ] This also might have influenced the variations observed by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysms were secured by microsurgical clipping or endovascular coiling, mostly within 24 h after admission. Post-interventional intensive care treatment of SAH patients in our center was already described elsewhere [ 11 , 43 ] [ 10 , 42 ]. In short, conservative management consisted of maintenance of normovolemia, mean arterial pressure >70 mmHg, and oral nimodipine for the first 21 days after ictus.…”
Section: Methodsmentioning
confidence: 99%